PENGARUH STRATEGI PROMOSI DI SOCIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK APPLE YANG DI MEDIASI WORD OF MOUTH MARKETING (Studi Kasus Pada Queeniphone Bengkulu) - Islamuddin Islamuddin; Ray Depa (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACT The purpose of this study was to determine The Effect of Promotion Strategies in Social Media toward Apple Brand Mobile Purchasing Decisions Mediated by Word of Mouth Marketing on Queen iphone Bengkulu. This research used survey research methods with quantitative data analysis by using the MSI method (method of successive interval) to transform ordinal scale data into interval scale data. The population of this study were all of consumers who buy Apple Brand Mobile products on Queeniphone Bengkulu. The results of this study know that there were significant effect toward Apple Brand Mobile Purchasing Decisions Mediated by Word of Mouth Marketing on Queen iphone Bengkulu. It is better for owner of Queen iphone Bengkulu to maintain and even improve consumer purchasing decisions by using variuos promotion strategy. Keywords: Promotion strategy, word of mouth marketing, purchasing decisions.